2022
DOI: 10.1007/s12098-021-04023-w
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antibiotic Overexposure and Adverse Outcomes in Very-Low-Birth-Weight Infants Without Culture-Proven Sepsis or Necrotizing Enterocolitis: A Multicenter Prospective Study

Abstract: Objectives To explore the associations between higher antibiotic use rates (AURs) and adverse outcomes in very-low-birth-weight (VLBW) infants without culture-proven sepsis or necrotizing enterocolitis (NEC) in a multicenter of China. Methods A prospective cohort study was performed on VLBW infants admitted to 24 neonatal intensive care units from January 1, 2018, to December 31, 2018. AUR was calculated as calendar days of antibiotic therapy divided by to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This is consistent with the authors’ previous report that in VLBW infants the total antibiotic use accounted for more than half of their entire hospital stay (mean AUR > 50%) in 24 NICUs of Hunan Province [ 9 ]. Similarly, Hou SS et al [ 19 ] reported an AUR of 56% in VLBW infants from 24 NICUs of the Northern China Neonatal Network. In the United States, Flannery et al [ 20 ] collected data from 297 NICUs and found that 78.6% of VLBW infants had early antibiotic initiation.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with the authors’ previous report that in VLBW infants the total antibiotic use accounted for more than half of their entire hospital stay (mean AUR > 50%) in 24 NICUs of Hunan Province [ 9 ]. Similarly, Hou SS et al [ 19 ] reported an AUR of 56% in VLBW infants from 24 NICUs of the Northern China Neonatal Network. In the United States, Flannery et al [ 20 ] collected data from 297 NICUs and found that 78.6% of VLBW infants had early antibiotic initiation.…”
Section: Discussionmentioning
confidence: 92%
“…218 The combination of dysbiosis and hyperoxia has also been linked to more severe disturbances in lung architecture in animal models. 219,220 Exposure to antibiotics both in the first week of life 221,222 and throughout the NICU stay 119 is associated with BPD, with evidence of a dose-response relationship. 119 Significantly higher odds of moderate-severe BPD were noted in a cohort of infants <32 weeks GA without risk factors for infection who were exposed to antibiotics within the 24 hr of life (OR: 2.30, 95% CI: 1.21-4.38).…”
Section: Early Course: First Week Of Life -Judicious Use Of Antimicro...mentioning
confidence: 99%
“…219,220 Exposure to antibiotics both in the first week of life 221,222 and throughout the NICU stay 119 is associated with BPD, with evidence of a dose-response relationship. 119 Significantly higher odds of moderate-severe BPD were noted in a cohort of infants <32 weeks GA without risk factors for infection who were exposed to antibiotics within the 24 hr of life (OR: 2.30, 95% CI: 1.21-4.38). 108 These results suggest that movement towards a selective approach to early antibiotic treatment may be a more effective BPD preventive strategy.…”
Section: Early Course: First Week Of Life -Judicious Use Of Antimicro...mentioning
confidence: 99%
See 1 more Smart Citation
“…The only indication for neonatal antibiotic use remains infection and sepsis [ 251 ]. Based on a novel multicenter prospective study, antibiotic overexposure triples the risk of BPD [ 252 ]. After exposure of human bronchial epithelioid cells to mechanical stretch, IL-13, metalloprotein-9, and transient receptor potential canonical 1 (TRCP1) are significantly increased within half an hour of the initiation of stretch stress [ 253 ].…”
Section: Rediscovering Old Drugsmentioning
confidence: 99%